2020
DOI: 10.1177/1043986220971394
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Process of Debt Collection in Community Corrections: The Case of the Monetary Compliance Unit

Abstract: Monetary sanctions levied on individuals on probation and parole may dramatically influence their ability to reintegrate into the community and to complete their community supervision. Yet very little work has empirically assessed how agencies respond to these obligations. This is critical, given that individuals under community supervision occupy a liminal space: free in the community yet often at risk of violation, rearrest, additional fines, or re-incarceration. In this article, we introduce an approach to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…Once payment plans are developed in this unit, they cannot be waived or modified in the future. A county in Pennsylvania uses a similar model (see Link et al, 2021), as do jurisdictions in Indiana. Other consequences.…”
Section: Consequences For Nonpaymentmentioning
confidence: 99%
“…Once payment plans are developed in this unit, they cannot be waived or modified in the future. A county in Pennsylvania uses a similar model (see Link et al, 2021), as do jurisdictions in Indiana. Other consequences.…”
Section: Consequences For Nonpaymentmentioning
confidence: 99%
“…Considered together, as well as contextualized with the data from the current study, this tension—highlighted in the observed ideological and practical variation across counties—poses significant challenges to developing actionable monetary sanction policy reform. Where policymakers seek avenues for community correctional reform (see Link et al 2020), either through abolition or incremental change, these findings suggest that many probation agencies are poorly positioned to adapt due to their practical reliance on this revenue and the varied landscape of assessed monetary sanctions. This mix of justifications may also challenge the development and implementation of reform-oriented legislation, especially if it attempts to institute broad, blanket policies regarding the assessment of fees, debt collection, and the use of means-testing given differences reflected in responses in this single state.…”
Section: Resultsmentioning
confidence: 99%
“…For example, bi-monthly (every other month) collection of a $20 monthly supervision fee will not affect the rate of accumulation of debt balance, only the rate of repayment. Consequently, individuals in such a scenario may stay on supervision longer, assuming that there are not mechanisms to forgive that debt when supervision terminates or to adjust supervision conditions in a manner more responsive to long-term debt collection (Link et al 2020). This response may not be universal across agencies but is possible given the distribution of responses.…”
Section: Discussionmentioning
confidence: 99%
“…Permissible ranges for fines, fees, and costs may be set by law and/or policy, but extralegal factors-such as race and age-can also impact the amount and type of assessed LFOs . Other studies show that Black persons have significantly higher LFO debt (Edwards and Harris 2020;Shannon 2020) and face more difficulty in repayment (Link 2019;Link et al 2021). Age is also important, as older persons possess more debt and seem to struggle to repay (Link et al 2021;Ruback and Clark 2011).…”
Section: Factors Affecting Repaymentmentioning
confidence: 98%
“…Other studies show that Black persons have significantly higher LFO debt (Edwards and Harris 2020;Shannon 2020) and face more difficulty in repayment (Link 2019;Link et al 2021). Age is also important, as older persons possess more debt and seem to struggle to repay (Link et al 2021;Ruback and Clark 2011).…”
Section: Factors Affecting Repaymentmentioning
confidence: 98%